Long-Term Results of ACL Reconstruction Using a Nonanatomic Double-Bundle Technique with Extra-Articular Reinforcement - Dalla-Rosa, J.; Espejo-Reina, A.; Tamimi, I.; Espejo-Reina, M. J.; Lombardo-Torre, M.; Espejo-Baena, A. (The Journal of Knee Surgery, 2019)
Extra-articular procedures for the improvement in rotational stability after anterior cruciate ligament (ACL) reconstruction have gained popularity in the last decade. This surgical gesture hoped to improve resistance to the high tensional forces affecting the ACL graft during cutting and pivoting movements of the lower extremity and eventually prevent ACL reconstruction failure. We performed this study to analyze the long-term results of patients undergoing ACL reconstruction using a nonanatomic double-bundle technique with an additional extra-articular augmentation. All the cases that underwent an ACL reconstruction using a nonanatomic double-bundle technique with an extra-articular reinforcement during the period between 1992 and 1997 were reviewed. The inclusion criteria for this study included a minimum follow-up of 10 years and age between 14 and 45 years at the time of the surgery. Forty patients were included in this series (34 males and 6 females). The mean Lysholm score after a minimum follow-up period of 10 years was 92.3 (standard deviation [SD], 9.4). The average preoperative Tegner score of the participants was 7.0 (SD, 1.1). This score decreased to 5.7 (SD, 1.2) at the end of follow-up. Follow-up X-rays were reviewed to assess the degenerative changes in the three knee compartments. Degenerative changes ≥ Kellgren–Lawrence grade 2 were observed in our six (15%) patients, all of them in the medial knee compartment. With these results, we conclude that double-bundle nonanatomic ACL reconstruction combined with an extra-articular reinforcement resembling the anterolateral ligament offers good overall long-term results, with relatively low rates of osteoarthritis.
Keywords: laxity; ACL; extraarticular; anterolateral; osteoarthritis